FinTech development for financial inclusiveness - Anshari, Muhammad, 1977-; Almunawar, Mohammad Nabil, 1960-; Masri, Masairol, 1974- (Business Science Reference, 2022)
"This book highlights how FinTech supports the availability and equality of opportunities to access financial services for individuals and businesses to take advantage of affordable, and timely financial products and services by featuring conceptual, case studies, recent development, best practices, comparative assessment, business processes, as well as strategies and outputs in studies of FinTech from multiple domains of knowledge"--